Acquired von Willebrand’s Syndrome in the Course of Waldenström’s Disease - Mazurier, Claudine; Parquet-Gernez, Armelle; Descamps, Jacques; Bauters, Francis; Goudemand, Maurice (Thrombosis and Haemostasis, 1980)
Acquired von Willebrand's syndrome with a regressive evolution is described in a 66 year old man with Waldenström's disease. An inhibitor electively directed against Ristocetin cofactor activity has been demonstrated, active in vitro after incubation at 37° C. Serum fractionation showed that the inhibitor was independant of the monoclonal IgM and subsequent purification that it was IgG in nature. The results permit its classification as an auto-antibody.
Keywords: Acquired von Willebrand's syndrome; Auto-antibody; Waldenström's disease